Patterns of Care Among Real‐World Patients with Metastatic Neuroendocrine Tumors. (23rd April 2019) - Klink, Andrew J.; Feinberg, Bruce; Yu, Hsing‐Ting; Ray, David; Pulgar, Sonia; Phan, Alexandria; Vinik, Aaron
Abstract: Background: Although recent pivotal trials (PROMID, CLARINET) have established somatostatin analogs (SSAs) as first‐line agents for neuroendocrine tumors (NETs), their use in clinical practice is largely unknown. We aimed to understand real‐world management and treatment of gastroenteropancreatic (GEP) NETs. Materials and Methods: Patients with metastatic GEP‐NETs treated with SSAs, lanreotide depot or octreotide long‐acting release (LAR), between January 1, 2015, and December 31, 2015, were identified from a U.S. claims database supplemented with chart review for a subset of patients. Descriptive statistics summarized patients' demographics, clinical characteristics, treatment patterns, and healthcare resource use. Univariate and multivariate comparisons were made across SSA groups. Results: Among 548 patients treated with an SSA for metastatic GEP‐NET (lanreotide = 108; octreotide = 440), demographic and clinical characteristics were similar across groups, except more patients with pancreatic NETs were treated with lanreotide (38.7% vs. 6.3%, p < .01). More octreotide patients had a diagnosis of carcinoid syndrome compared with lanreotide patients (19.8% vs. 11.1%, p = .02). Approximately 1.1% of patients received lanreotide (>120 mg every 4 weeks [Q4W]) at a dose above label compared with 12.7% of octreotide patients (>30 mg Q4W; p < .01). At 1.5 years after SSA initiation, 85.7% (95% confidence interval, 74.3%–92.3%) were still on index SSA as reported by the physician. Variances between chart review and claims data were significant. Conclusion: SSAs were common in first‐line systemic intervention, but dose escalations and dosing deviations outside of label were noted. Variances between claims and chart review warrant additional research to compare methodologies. With an increasing focus on value‐based care in oncology, it is critical to understand the use of, and outcomes with, these agents in community practices. Implications for Practice: The aim of this study was to enhance understanding of real‐world management and treatment of metastatic neuroendocrine tumors (NETs), with particular focus on systemic therapy with a somatostatin analog (SSA). As per published guidelines, SSAs are common in first‐line systemic intervention, but dose escalations and dosing deviations outside of the label are noted for symptom control. Nevertheless, oncologists must weigh the implications of the use of above‐label dosing of SSAs to manage and treat patients with metastatic NET within a value‐based care framework. Abstract : This article reports on the real‐world patient characteristics and treatment of gastroenteropancreatic neuroendocrine tumors: the SSA dosing and frequency patterns, health care resource utilization, and the use of concurrent locoregional and systemic therapy. With an increasing focus on value‐based care in oncology, it is critical to understand how these agents are used in routine, community‐based practices and how outcomes are associated with varying patterns of their usage.